From Ceramics to Ceramic Steel: Genesis - Maller, Udita S; Thangaraj, Deepa Natesan; Maller, Sudhakar (Journal of Orofacial Research, 2012)
Ceramics were introduced in dentistry since the 16th century as dental porcelain, primarily for the manufacture of porcelain teeth. Improved technology saw porcelain jacket crowns, metal ceramic systems with better bonding techniques of different alloys to porcelain, bonded foil systems and then the introduction of alumina and other oxides, such as zirconia tostrengthen ceramics. Superior processing methods and sintering technologies have lead to CAD/CAM ceramics and the all ceramic systems. This article provides an overview ofthe different methods of strengthening ceramics for a better understanding of the mechanisms involved, including that of the support system.